2020
DOI: 10.1021/acs.iecr.9b06343
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Solid Mixing in Bubbling Fluidized Beds via Two-Fluid Model Simulations

Abstract: The influence of particle density and fluidization velocity on the mixing behavior of Geldart B particles was investigated in bubbling fluidized beds for various operating conditions using a two-fluid model approach. The simulation results proved that the predicted solid flow pattern for a wide range of Geldart B particles differs from particles of Geldart B/D classification at identical fluidization numbers. Quantitative analysis of the predicted solid velocity variances revealed that the solid axial dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Micromixing is associated with mixing due to the fluctuation of solid particles’ velocity, quantified by granular temperature. 27 On the other hand, macromixing is attributed to solids mixing due to the motion of bubbles in the fluidized bed, quantified by the solids velocity variance. 27 More information about the mixing can be found in our previous works.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Micromixing is associated with mixing due to the fluctuation of solid particles’ velocity, quantified by granular temperature. 27 On the other hand, macromixing is attributed to solids mixing due to the motion of bubbles in the fluidized bed, quantified by the solids velocity variance. 27 More information about the mixing can be found in our previous works.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the variance of the hydrodynamic velocity is of high relevance to quantify macromixing. 33 In this regard, the solids velocity variance tensor was computed using the following equation in each computational cell 27 where v ® and v ( t k ) represent the time-averaged and instantaneous solids velocity in the computational cell, respectively. ⊗ denotes the dyadic product.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Differing from the CFD-DEM model, the two-fluid model (TFM) is also applied. , Hernández-Jiménez et al used the TFM to study solid dispersion by setting two types of solid phases and evaluating the mixing completion level according to the relative volume fraction of two solid fluids. They found that it took little time to reach complete mixing with smaller particle sizes.…”
Section: Introductionmentioning
confidence: 99%